Intramedullary tumors. Recent experience - Zubillaga, Lucas; Pereyra, Julieta; Jaikin, Mario S. (Revista Argentina de Neurocirugía, 2020)
Introduction: Intramedullary tumors constitute an infrequent pathology, being capable of radical resection with a high risk of definitive neurological deterioration.Objectives: Evaluate outcome determinants such as the surgical technique used, the usefulness of neurophysiological monitoring and the evolution of the cases recently treated in our Hospital.Material and Methods: We retrospectively reviewed the clinical records of patients diagnosed as spinal tumors between December 2011 and December 2018. The pre and post-operative neurological examination, tumor extension, description of the surgical technique and the information obtained during neurophysiological monitoring are recorded. The evolution was analyzed by the McCormick Scale, at 6 and 12 months. Admission and postoperative MRIs were compared to determine the degree of resection. Orthopedic stabilization procedures as well as complementary oncological treatment were studied.Results: Follow up: 6 months to 5 years. 7 Female, 6 Male. Average age: 8 years (8 months to 14 years) Symptoms: Gait disturbance: 5, Pain: 5, Scoliosis: 4, Bladder Disturbance: 3, Tortícolis: 2.MRI: Solid 8, Solid/ cystic 5, associated Syrinx: 5Surgery: Laminoplasty: 11. Laminectomy: 2. Surgery monitoring : flattened wave less to  50%: 5, up to 50%: 6.Gross total removal: 7, Subtotal/Partial: 4, Biopsy: 2. New exploration: a patient with anterior spinal cord remained  Ependymoma.Surgical results: Worsened : 3. Unchanged: 5. Improvement: 5Chemotherapy : 2. Improvement of functional deficit was seen in 11 cases between 6-12 months. There were no deaths due the surgery.Conclusions: Worsening of neurological function is usual immediately to intramedullary surgery. Mostly of patients will have a recovery. Radical resection of this tumors is feasible and in some cases curative, in other cases provide better chemotherapy opportunities.
Keywords: Intramedullary Tumors; Surgery; Monitoring; Follow Up